State-specific heavy-atom effect on intersystem crossing processes in 2-thiothymine: A potential photodynamic therapy photosensitizer - Cui, Ganglong; Fang, Wei-hai (The Journal of chemical physics, 2013)
Thiothymidine has a potential application as a photosensitizer in cancer photodynamic therapy (PDT). As the chromophore of thiothymidine, 2-thiothymine exhibits ultrahigh quantum yield of intersystem crossing to the lowest triplet state T1 (ca. 100%), which contrasts with the excited-state behavior of the natural thymine that dissipates excess electronic energy via ultrafast internal conversion to the ground state. In this work, we employed high-level complete-active space self-consistent field and its second-order perturbation methods to explore the photophysical mechanism of a 2-thiothymine model. We have optimized the minimum energy structures in the low-lying seven electronic states, as well as ten intersection points. On the basis of the computed potential energy profiles and spin-orbit couplings, we proposed three competitive, efficient nonadiabatic pathways to the lowest triplet state T1 from the initially populated singlet state S2. The suggested mechanistic scenario explains well the recent experimental phenomena. The origin responsible for the distinct photophysical behaviors between thymine and 2-thiothymine is ascribed to the heavy-atom effect, which is significantly enhanced in the latter. Additionally, this heavy-atom effect is found to be state-specific, which could in principle be used to tune the photophysics of 2-thiothymine. The present high-level electronic structure calculations also contribute to understand the working mechanism of thiothymidine in PDT.